First Lebanese Antibiotic Awareness Week campaign: knowledge, attitudes and practices towards antibiotics. Issue 4 (April 2019) - Al Omari, S.; Al Mir, H.; Wrayde, S.; Merhabi, S.; Dhaybi, I.; Jamal, S.; Chahine, M.; Bayaa, R.; Tourba, F.; Tantawi, H.; Al Atrouni, A.; El Omari, K.; et al.
Summary: Antibiotic resistance (ABR) is a major global health threat that increases the risk of treatment failure and increases medical costs. One of the most common factors contributing to the spread of ABR is self-medication. The public, as well as workers in clinical and veterinary sectors, commit false practices towards appropriate antibiotic use, favouring the spread of resistance. As such, the first Lebanese Antibiotic Awareness Week campaign was initiated with a human-centred and interactive approach. The data showed a strikingly low level of antibiotic awareness. Cooperation between relevant stakeholders, policy-makers and health actors is crucial to control and overcome the problem of ABR.